Relación de los fundamentos teóricos-metodológicos de la pedagogía activa con el aprendizaje de los estudiantes de tercer año de educación básica de la unidad educativa Caracol, cantón Babahoyo, provincia de los Ríos, durante el periodo lectivo 2017 - Cedeño Bajaña, Joaquín René (2017)
The theme raised in this research, is entitled: relationship of the theoretical-methodological foundations of active pedagogy with the learning of third-year students of basic education snail educational unit, Babahoyo canton, province of rivers, during the 2017 school year. It has its origin in the detection of several classroom problems, associated with memorizing and repeating, based on individual efforts always with the purpose of competition. The justification of this research work gives an account of the reasons why we consider it pertinent and of academic impact, and the aforementioned background serves as a confirmation of the importance of this approach. This document is conveniently based on science, which is reflected in the conceptual framework and the theoretical position. Also here is the section of surveys, whose intention is to know what they think about this problem, the different actors of the educational act. These have been tabulated, interpreted and synthesized in the conclusions with their respective recommendations. Finally, we describe the proposal, which proposes the solution alternative to the problem detailed initially.